2023
DOI: 10.3390/resources12100126
|View full text |Cite
|
Sign up to set email alerts
|

Surimi Production from Tropical Mackerel: A Simple Washing Strategy for Better Utilization of Dark-Fleshed Fish Resources

Worawan Panpipat,
Porntip Thongkam,
Suppanyoo Boonmalee
et al.

Abstract: Mackerel (Auxis thazard), a tropical dark-fleshed fish, is currently a viable resource for the manufacture of surimi, but the optimal washing procedure for more efficient use of this particular species is required right away. Washing is the most critical stage in surimi production to ensure optimal gelation with odorless and colorless surimi. The goal of this study was to set a simple washing medium to the test for making mackerel surimi. Washing was performed three times with different media. T1 was washed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Instead, the Priacanthus sp increased the TPA value. Decapterus sp is a pelagic fish that contains dark muscle, as noted by Panpipat et al (2023) dark muscle is less effective for gelation compared to light muscle, primarily due to its higher content of sarcoplasmic proteins and lipids. Sarcoplasmic proteins negatively influenced the strength, deformability, and colour of gels made from fish myofibril proteins.…”
Section: Textural Profilementioning
confidence: 99%
“…Instead, the Priacanthus sp increased the TPA value. Decapterus sp is a pelagic fish that contains dark muscle, as noted by Panpipat et al (2023) dark muscle is less effective for gelation compared to light muscle, primarily due to its higher content of sarcoplasmic proteins and lipids. Sarcoplasmic proteins negatively influenced the strength, deformability, and colour of gels made from fish myofibril proteins.…”
Section: Textural Profilementioning
confidence: 99%
“…Surimi gel microstructure examination was carried out using the scanning electron microscope (SEM) (GeminiSEM, Carl Ziess Microscopy, Oberkochen, Germany) [2]. Samples with a thickness of 2-3 mm were fixed with 2.5% (v/v) glutaraldehyde in 0.2 M phosphate buffer (pH 7.2) for 2 h. The samples were then rinsed for 1 h in distilled water before being dehydrated in ethanol with serial concentrations of 50, 70, 80, 90, and 100% (v/v).…”
Section: Analysis Of Microstructurementioning
confidence: 99%
“…SEM images revealed that the microstructure of the gel samples differed (Figure 5). An ideal surimi gel had finer and more ordered networks, whereas a poor gel had a discontinuous network with bigger pores [2][3][4]. Surimi gel without lecithin (Figure 5a) exhibited heterogeneous aggregates with occasional spaces, as well as minute particle clots and a continually tightly packed structure.…”
Section: Microstructurementioning
confidence: 99%
See 2 more Smart Citations